Online Learning Readiness, Academic Resilience, and Subjective Well-Being of Junior High School Students during the COVID 19 Pandemic - Nadhila Safitri; Sumedi P Nugraha (Universitas Ahmad Dahlan, 2021)
Online learning process in COVID-19 pandemic can decline the quality of subjective well-being of students. The constraints faced by the students in doing the online learning can make them more frequently feel negative emotions such as being anxious, stressful, confused or bored. The aim of this study is to test the online learning readiness and academic resilience on the subjective well-being among students. A number of previous researches showed that the students ready to have online learning and having a good academic resilience could increase their subjective well-being. This study involved 200 students of Junior High School ‘X’ Lampung having online learning. It used three instruments: (a) scale of positive and negative experience (SPANE) (Diener, Wirtz, Tov, Kim-Prieto, Choi, Oishi, & Biswas-Diener, 2009), (b) academic resilience scale (Martin & Marsh, 2006), and (c) scale of student’s e-learning readiness questionnaire (Aydin & Tasci, 2005). The test of hypothesis used the Doubled Regression Analysis Technique (SPSS 20). The results of this study showed that the online learning readiness and academic resilience simultaneously were effective in determining the subjective well-being of students (R = 0.09, p < 0.01).Keywords: subjective well-being, academic resilience, online learning readiness, pandemic COVID-19.